The Diffusion of E-commerce at the Firm Level: Theoretical Implications and Empirical Evidence - Enrico Santarelli; Samuele D'Altri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2001)
As a specific institution of distributive trades, e-commerce displays similarities with retail stores and mail ordercompanies. As well as providing theoretical support for the assumption that e-commerce is a way to sell certain goods and services at prices potentially lower than those of traditional distributive channels, this paper analyses its inter-firm diffusion among a sample of firms (mostly SMEs) in Italy. The paper has three main purposes. Firstly, it challenges the view of e-commerce as a "technological revolution", by pointing out its nature as a costminimizing marketing channel. In particular, it shows how, under certain circumstances, e-commerce is a source of transaction cost advantages analogous to those yielded by mail order business. Secondly, the paper identifies the circumstances under which e-commerce sales might achieve a significant level of penetration among those SMEs that would otherwise incur high costs in organizing a proprietary distributive channel. Thirdly, the paper employs a unique data set of Italian manufacturing, service, and hospitality firms (nearly 90% of them with fewer than 100 employees) to estimate a diffusion model based on the logistic curve. According to the estimates, by the fourth quarter of 2003 nearly 50% of the population of firms in the geographical area surveyed will have introduced e-commerce among their marketing channels.
Keywords: 330